1997
DOI: 10.1139/x97-121
|View full text |Cite
|
Sign up to set email alerts
|

Ozone effects on seedling sugar maple (Acer saccharum) and yellow-poplar (Liriodendron tulipifera): gas exchange

Abstract: The effects of one to two seasons of ozone (O 3 ) exposure ranging from subambient to 1.7 times ambient on the gas exchange of sugar maple (Acer saccharum Marsh.) and yellow-poplar (Liriodendron tulipifera L.) were studied in standard 3 m diameter open-top chambers. Cumulative O 3 exposures based on SUM00 index ranged from 16 to 107 ppm⋅h in 1990 and 31 to 197 ppm⋅h in 1991. During the 120-day exposure in 1990, rates of net photosynthesis and stomatal conductance of sugar maple foliage were not affected by O 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…These seedlings were harvested at the same dates and biomass accumulation at the end of the second season of exposure did not decrease compared with the control seedlings (data not shown). Similar results were reported for sugar maple seedlings by Rebbeck and Loats (1997) and Scherzer (1991) after exposure to 304 ppm h O3 and 199 ppm h O3 respectively over two growing seasons.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These seedlings were harvested at the same dates and biomass accumulation at the end of the second season of exposure did not decrease compared with the control seedlings (data not shown). Similar results were reported for sugar maple seedlings by Rebbeck and Loats (1997) and Scherzer (1991) after exposure to 304 ppm h O3 and 199 ppm h O3 respectively over two growing seasons.…”
Section: Discussionsupporting
confidence: 88%
“…However, increasing O3 levels may impose more frequent oxidative stress periods, which may counteract this advantage (Rebbeck and Scherzer 2002;Rebbeck et al 2004;Riikonen et al 2005). Sugar maple has been reported as a tolerant species to O3 (Laurence et al 1996;Rebbeck and Loats 1997). However, other studies have shown that this species can be affected by O3 (Kress and Skelly 1982;Tjoelker et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the +O 3 treatment has had little effect relative to ambient on the L mass of either species in the aspen-maple community (Figure 4). Although maple (Acer saccharum) is relatively insensitive to elevated O 3 (Noble and others 1992;Rebbeck and Loats 1997), we are not able to explain why there has been no reduction in aspen leaf mass in this community. For the aspen-only community, Kubiske and others (2007) found using measurements of tree survival and stem volume during the first 8 years of the experiment that the +O 3 treatment had diminished the relative importance of O 3 -sensitive clones and increased the importance of O 3 -tolerant clones.…”
Section: Changes In Co 2 and O 3 Effects Through Timecontrasting
confidence: 57%
“…Measurements were taken over 3 days with one treatment replicate completed per day. Since yellowpoplar photosynthetic rates were determined to be saturated at 800 mmol m 2 s 1 PAR (photosynthetically active radiation) (Loats and Rebbeck 1999;Rebbeck and Loats 1997), leaves were illuminated with an artificial light (GE Cool-Beam PAR Lamp Model 300PAR 56/2WFL) when ambient light dropped below saturating conditions. Leaves were measured at the CO 2 concentration at which they were grown.…”
Section: Treatment and Seasonal Effectsmentioning
confidence: 99%